HIJAB IN INDONESIAN ONLINE MEDIA - Auliyasani, Nurul (2014)
The present study is designed to investigate how hijab is verbally and visually represented in Indonesian online media and to construe the representation in depth. A descriptive qualitative method was used by employing a multimodal analysis along with corpus linguistics as a tool for collecting the data. The data were taken from 150 articles about hijab in three Indonesian news websites, namely, Kompas, Republika and Detik. The data then were processed with software named Concordance. Transitivity system (Halliday, 1994) was used to analyze verbal text data and Visual Grammar (Kress & van Leeuwen, 2006) for the visual one. The study found that hijab is generally represented as an identity symbol for Moslem women. In Indonesia online media, the representation of women wearing hijab considered as a new distinctive identity when it is related to somebody's change of appearance. In addition, it is also represented as a symbol of Moslem women empowerment in a way that women wearing hijab does not limit what women can do. Furthermore, hijab has become a commodity product in Indonesia fashion industry. It is contrary to the representation found related to the Western view. In line with some previous studies, in Indonesian online media, it is also reported that hijab symbolizes minority in some Western countries. Keywords: Multimodal Analysis, Transitivity System, Visual Grammar, Corpus Linguistics. Penelitian ini didesain untuk menginvestigasi bagaimana hijab direpresentasikan secara verbal dan secara visual pada media online di Indonesia serta menguraikannya lebih dalam. Metode deskriptif kualitatif digunakan dengan memakai analisis multimodal dan corpus linguistics sebagai alat untuk mengumpulkan datanya. Data pada penelitian ini diambil dari 150 artikel tentang hijab pada tiga website berita di Indonesia, yaitu Kompas, Republika dan Detik. Data tersebut kemudian diolah dengan menggunakan software bernama Concordance. Transitivity system (Halliday, 1994) digunakan untuk menganalisis data teks verbal dan Visual Grammar (Kress and van Leeuwen, 2006) untuk menganalisis data teks visual. Penelitian ini menemukan bahwa hijab, secara general, direpresentasikan sebagai simbol identitas bagi perempuan Muslim. Pada media online di Indonesia, representasi dari hijab yang digunakan oleh kaum perempuan adalah sebagai suatu identitas pembeda baru saat berkaitan dengan perubahan penampilan seseorang. Selain itu, hijab juga direpresentasikan sebagai simbol dari pemberdayaan perempuan Muslim dalam kaitannya dengan penggunaan hijab yang tidak membatasi kaum perempuan. Lebih jauh, hijab telah menjadi produk komoditas di industri fashion di Indonesia. Hal tersebut bertentangan dengan representasi yang ditemukan pada pandangan Barat. Sementara itu, sejalan dengan beberapa penelitian sebelumnya, hijab pada media online di Indonesia juga menunjukkan bahwa hijab menyimbolkan minoritas di beberapa negara Barat. Kata Kunci: Multimodal Analysis, Transitivity System, Visual Grammar, Corpus Linguistics.